Do Workers Really Benefit From Their Social Networks? - François Fontaine (Institute for the Study of Labor (IZA), 2004)
This paper provides a simple matching model in which unemployed workers and employers in large firms can be matched together through social networks or through more "formal" methods of search. We show that networks do not necessarily add new externalities and that some results previously obtained in the literature are questionable. Nevertheless, social networks can, in some case, substitute for labor market and this crowding-out effect may be socially costly. We show that a policy increasing the number of workers embedded in the social networks can increase the unemployment rate and decrease workers welfare. Since it is mostly the firms which benefit from larger social networks, transfers from the firms to the workers are necessary to make larger access to the social networks efficient.
Keywords: Z13; J68; E24; J64; 330; economic policy; matching; social networks; unemployment; Arbeitslosigkeit; Arbeitsnachfrage; Matching; Soziales Netzwerk; Crowding out; Arbeitsmarkttheorie; Theorie